Information Technology Governance Disclosure in Annual Report of Indonesia Financial Institutions - Weli Weli (Bina Nusantara University, 2020)
The research aims to analyze the level of information technology (IT) governance disclosure in the annual report of financial companies and influencing factors in the exposure of IT governance. It distinguishes financial companies into two groups, namely banking and non-banking financial sectors. The data collection method used is the content analysis of the 2017 annual report from the companies. The results of 76 financial companies show that the level of IT governance disclosure by financial companies in Indonesia is higher than in previous studies in southern Africa and Belgium. Data analysis also shows that the determinants of IT governance disclosure are different in the two groups of companies. The determinant of IT governance disclosure for the banking industry is profitability, while the nonbanking financial sector is the company size.